COVID-19 impact and vaccine effectiveness among healthcare workers of a large University Hospital in Lombardy, Italy - Mendola, Marco; Tonelli, Fabio; Garletti, Francesca Stefania; Greco, Daniela; Fiscella, Michela; Cucchi, Isabella; Costa, Maria Cristina; Carrer, Paolo (La Medicina del Lavoro, 2021)
Background: Healthcare Workers (HCWs) are a key element in managing the COVID-19 pandemic, but they are also at high risk of infection. Objective: The aim of this study was to describe, in a large university hospital which provided healthcare services to patients with SARS-CoV-2 infection, the course of the epidemic among HCWs and effectiveness of COVID-19 vaccination in reducing SARS-CoV-2 infection and disease. Methods: Our case series included all “Fatebenefratelli Sacco” University Hospital workers. Data were collected until the 15th of May 2021 and analysed as part of the health surveillance program carried out by the Occupational Health Unit. Results: From March 2020 until May 2021, 14.4% of workers contracted COVID-19, with the highest incidence peak recorded during the second wave of the pandemic. The prevalence of infection was slightly higher in males than in females, and a greater number of cases was found in job categories characterized by direct patient care activities. We reported a higher prevalence of “serious/critical illness” in elder workers. A clear reduction of COVID-19 incidence was found in our population during the third pandemic wave, that coincided with the start of vaccination campaign. Discussion: HCWs have been at high risk of COVID-19 infection. Male sex and advanced age appear to be predisposing factor and negative prognostic factor respectively. An out-of-hospital setting appears to be the main source of COVID-19 confirming that the correct use of protective devices during work counters the risk of infection. Vaccination seems to reduce both documented cases of infection and severe illness.